2017
DOI: 10.1158/1538-7445.sabcs16-s6-04
|View full text |Cite
|
Sign up to set email alerts
|

Abstract S6-04: The PI3K inhibitor, taselisib, has enhanced potency in PIK3CA mutant models through a unique mechanism of action

Abstract: Alterations of the phosphoinositide-3 kinase (PI3K)/Akt signaling pathway occur broadly in cancer via multiple mechanisms including mutational activation of the PIK3CA gene. The dysregulation of this pathway has been implicated in tumor cell growth and survival, thus PI3K is a promising therapeutic target with multiple inhibitors in clinical trials. Taselisib (GDC-0032), a novel, oral, selective inhibitor of p110alpha, sparing inhibition of p110beta, is more potent against cancer cells bearing mutations in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…Taselisib has increased potency against the mutant version of the PI3K alpha isoform, as demonstrated in chemical assays as well as in cancer cell lines (6). A higher therapeutic window due to greater selectivity for PIK3CA mutant isoforms has been shown in extensive laboratory studies (21) and is also suggested by the fact that partial responses were only observed in patients with PIK3CA-mutant tumors. The other indirect evidence for an enhanced therapeutic window is that at the chosen recommended dose, patients were able to stay on the study agent for prolonged periods of time.…”
Section: Discussionmentioning
confidence: 82%
“…Taselisib has increased potency against the mutant version of the PI3K alpha isoform, as demonstrated in chemical assays as well as in cancer cell lines (6). A higher therapeutic window due to greater selectivity for PIK3CA mutant isoforms has been shown in extensive laboratory studies (21) and is also suggested by the fact that partial responses were only observed in patients with PIK3CA-mutant tumors. The other indirect evidence for an enhanced therapeutic window is that at the chosen recommended dose, patients were able to stay on the study agent for prolonged periods of time.…”
Section: Discussionmentioning
confidence: 82%
“…Early clinical trials of the isoform-selective inhibitors, alpelisib and taselisib, in breast cancer have produced results consistent with a previous meta-analysis of clinical trials of PI3K pathway inhibitors in patients with diverse cancers, revealing that patients with H1047R mutations had higher response rates than those with other PIK3CA mutations, or no mutations in this gene (Janku et al, 2013; Mayer et al, 2017). The p110β-sparing inhibitor, taselisib, (Table S1) was reported to induce degradation of mutant p110α (Friedman et al, 2017). It is conceivable that distinct activating mutations in p110α might confer differential susceptibilities drug-induced degradation; if this proves to be the case, perhaps drug-induced turnover of the p110α H1047R mutant underlies the increased taselisib sensitivity of tumors expressing this particular p110α oncoprotein.…”
Section: Therapeutic Targeting Of the Pi3k Pathway In Cancermentioning
confidence: 99%
“…Tumor PIK3CA H1047R in cancer cells in culture and patient-derived xenografts (PDX) without significant change in WT p110α (62). It spares p110β but also inhibits p110γ and p110δ.…”
Section: Pi3k Pi3kmentioning
confidence: 99%